2017
DOI: 10.1002/2211-5463.12306
|View full text |Cite
|
Sign up to set email alerts
|

Rb‐independent E2F3 promotes cell proliferation and alters expression of genes involved in metabolism and inflammation

Abstract: E2F transcription factors are key targets of the retinoblastoma (Rb) tumor suppressor. Despite extensive studies, the in vivo consequences of disrupting the interaction between Rb and an individual E2F are not clear. Here, we report an E2F mutation that interfered with binding to Rb family proteins without significantly affecting protein level or transactivation function. Characterization of mouse embryonic fibroblasts with this Rb‐independent E2F3LQ mutation revealed that disrupting the Rb and E2F3 interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Recent studies have also shown that E2F3 is positively correlated with the regulation of cell cycle in organisms and it has an effect on biological functions such as cell proliferation and apoptosis [50][51][52]. Evidence points out that targeted therapy of cervical cancer can be achieved by reducing E2F3 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that E2F3 is positively correlated with the regulation of cell cycle in organisms and it has an effect on biological functions such as cell proliferation and apoptosis [50][51][52]. Evidence points out that targeted therapy of cervical cancer can be achieved by reducing E2F3 [53].…”
Section: Discussionmentioning
confidence: 99%
“…E2F2, E2F3 and E2F8 were significantly up-regulated in asthmatic horses only, while E2F1 was significantly down-regulated in non-asthmatics. E2F transcription factors are crucial in regulating cell cycle 56 , lung development 57 and transcriptional programs for inflammation, immunity, metabolism and stress-response 58 . E2Fs factors can have redundancy in function through either promotion or repression of transcription, sometimes shifting function under different conditions, such as different development stages 59 .…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, we introduced the LQ mutation into mouse E2F3 to generate E2F3 LQ/LQ knockin mice and characterized the effect of E2F3 LQ/LQ mutation in mouse embryonic fibroblasts (18). Here we describe the characterization of the effect of Rb-family independent E2F3 LQ/LQ mutation on mammary gland remodeling during pregnancy.…”
mentioning
confidence: 96%
“…Importantly, the dE2F1 su89 mutation disrupts dE2F1's interaction with fly Rb without affecting the transcription activation function and can activate E2F target gene expression in the presence of fly Rb proteins (17). Additionally, the LQ mutation in the human C-terminal E2F1 peptide significantly decreased peptide binding to the Rb protein and more dramatically to the Rb family protein p107 (18). Furthermore, the same LQ mutation in the full length mammalian activating E2F proteins also impaired binding of these E2F proteins to the Rb protein without significantly affecting E2F protein levels or the ability to activate transcription (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation